Demented Prisoners - Klaus Kultti; Hannu Salonen (Aboa Centre for Economics (ACE), 2009)
We study infinitely repeated Prisoners' Dilemma, where one of the players may be demented. If a player gets demented in period t after his choice of action, he is stuck to this choice for the rest of the game. So if his last choice was "cooperate" just before dementia struck him, then he's bound to cooperate always in the future. Even though a demented player cannot make choices any more he enjoys the same payoffs from strategy profiles as he did when healthy. A player may prove he is still healthy by showing a (costly) health certificate. This is possible only as long as the player really is healthy: a demented player cannot get a clean bill of health. We study an asymmetric information game where it is known that player 1 cannot get demented but player 2 may be either a "healthy" type who will never be demented or a "dementible" type who eventually will get demented. We study when cooperation can be maintained in a perfect Bayesian equilibrium with at most health check.
Keywords: C72; 330; prisoners' dilemma; dementia; co-operation